An evaluation of motivational policies in enhancing employee performance in parastatals : a case of the Rural Electrification Agency - Marimira, Nyasha Elizabeth (Midlands State University, 2020)
Motivation is crucial for organizations to function; without motivation employees will not put up their best and the organisations performance would be less efficient. The situation is even more serious in developing countries where working conditions are unattractive. It is in view of this that this study was conducted to assess the role of motivation on employee performance in parastatals: a case study of the rural electrification agency. The case-study approach was adopted for the study with both qualitative and quantitative techniques such as stratified sampling and accidental sampling techniques were employed. Key informant interviews and questionnaires were the methods of data collection for the study and SPSS software was used to analyse data collected from the field. The study found that, motivation packages for the staff of REA were inadequate. Monetary rewards and a conducive working environment were the preferred form of motivation for workers. The effects of poor motivation on work performance at REA were absenteeism, low output and high labour turnover. The study therefore, recommends that management should implement motivational policies